Possibilities of Biogas in Urban Context - Koirala, Srijana (Journal of the Institute of Engineering, 2020)
Increasing population and rapid development in the planet earth have resulted in increasing demand of energy sources. Developed countries have adopted renewable sources in their policy for a sustainable future but, developing countries like Nepal are still lagging behind. Petroleum gas is used by all the city dwellers which is imported from neighboring countries and is not sustainable for a long term. Rapid urban growth has brought solid waste management and energy demand as a great challenge. Production of energy through biogas can help in management of bio-degradable waste as well as fulfill energy demands. This paper highlights study of large-scale biogas plant in and outside Nepal and explains how they have helped in managing waste, fulfilling energy demands and made positive impact in the community. This paper also suggests on possibilities of biogas as an alternative energy in developing scenario of Nepal.